2016
DOI: 10.1016/j.yrtph.2016.07.019
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the results from intra-pleural and intra-peritoneal studies with those from inhalation and intratracheal tests for the assessment of pulmonary responses to inhalable dusts and fibres

Abstract: The aim of this paper is to compare results from inhalation studies with those from intraperitoneal and intrapleural tests, where available, for a number of fibrous and particulate test materials. The objective is to determine how well intraperitoneal/intrapleural studies predict the pathological responses observed in more standard in vivo studies of pulmonary toxicity, with a particular focus on carcinogenicity. Published toxicity data was obtained for a number of materials including asbestos, wollastonite, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 70 publications
1
16
0
Order By: Relevance
“…To resolve these problems and determine whether further experimentation on the carcinogenicity of POT fibers is warranted, we conducted a short‐term experiment comparing the intensity of early indicators of possible carcinogenicity in rats given POT fibers or non‐fibrous titanium dioxide nanoparticles (nTiO 2 ). We used two types of nTiO 2 , photoreactive anatase (a‐nTiO 2 ) and inert rutile (r‐nTiO 2 ): a‐nTiO 2 is a weak carcinogen in the lung that induces neoplastic development when high doses are given . The major component of these materials is titanium but the shapes (granular particles, short rods, and long needle‐like‐shaped fibers) are different.…”
Section: Introductionmentioning
confidence: 99%
“…To resolve these problems and determine whether further experimentation on the carcinogenicity of POT fibers is warranted, we conducted a short‐term experiment comparing the intensity of early indicators of possible carcinogenicity in rats given POT fibers or non‐fibrous titanium dioxide nanoparticles (nTiO 2 ). We used two types of nTiO 2 , photoreactive anatase (a‐nTiO 2 ) and inert rutile (r‐nTiO 2 ): a‐nTiO 2 is a weak carcinogen in the lung that induces neoplastic development when high doses are given . The major component of these materials is titanium but the shapes (granular particles, short rods, and long needle‐like‐shaped fibers) are different.…”
Section: Introductionmentioning
confidence: 99%
“…This classification was reaffirmed by a subsequent Working Group meeting in 2001 (IARC, 2002), which concluded that there was sufficient evidence in experimental animals but inadequate evidence in humans for the carcinogenicity of refractory ceramic fibers. Later analyzes, however, indicated that the RCC animal studies were compromised by overload, a factor that has made it difficult to derive accurate estimates of risk by extrapolation of animal study results (Brown et al, 2005;Drummond et al, 2016;Greim et al, 2014;Maxim et al, 2003;NIOSH, 2006;Utell & Maxim, 2010). Notwithstanding limitations of the animal studies, these results prompted Figure 1.…”
Section: Animal Tests and Hazard Classificationmentioning
confidence: 99%
“…While the issue of the simultaneous effect of asbestos and other mineral particles needs to be further explored in reality, the hypothesis of a synergistic joint effect needs to be considered. Drummond et al (2016) published a review article that examined the relationship between the results of intra-pleural and intraperitoneal studies with those from inhalation and intratracheal tests for the assessment of pulmonary responses to inhalable dust and fibers. They concluded:…”
Section: Other Analysesmentioning
confidence: 99%
“…Moreover, pulmonary fibrosis has been highlighted as an effect of MWCNT exposure (Sharma et al 2016 ; Vietti et al 2016 ). Intraperitoneal injection, described as the most sensitive method for carcinogenicity testing of fibers (Bernstein et al 2001 ; Drummond et al 2016 ) has revealed a relation between curvature and carcinogenic potency of MWCNTs. However, due to its sensitivity this method is useful for hazard identification and studying mechanisms of action, its applicability to risk assessment remains to be established.…”
Section: Toxicity and Ecotoxicity Testing Of Nanomaterialsmentioning
confidence: 99%